Judicial Analysis of Banking Criminal Actions Related To Law Number 10 of 1998 - Verdy Isdiyanto; Benny Rory Wijaya; Agus Hariyono; Haidir Rahman (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
Banking has the main function as an intermediary, namely collecting funds from the public and channeling them effectively and efficiently to the real sectors to drive the development and stability of a country's economy, the bank bears a large reputation risk. Banks must always maintain the level of trust of customers or the public in order to save their funds in banks, and banks can channel these funds to drive the nation's economy. Banking criminal acts are basically acts against the law carried out, whether intentionally or unintentionally related to institutions, instruments and banking products, so that they cause religious and / or material mischief for the banks themselves or for customers or other third parties. Various kinds of laws and regulations have been issued by the government in the context of overcoming mistakes, negligence, and intentional actions of these insiders.